The safety and feasibility of thoracoscopic uncommon pulmonary segmentectomy - Igai, Hitoshi; Kamiyoshihara, Mitsuhiro; Yoshikawa, Ryohei; Osawa, Fumi; Yazawa, Tomohiro (Journal of Thoracic Disease, 2019)
Backgrounds: Opportunities to treat patients requiring uncommon pulmonary segmentectomy are increasing because small pulmonary nodules are being incidentally detected more often. Uncommon segmentectomy is frequently performed via thoracotomy because uncommon pulmonary segmentectomies are associated with various technical difficulties compared to common segmentectomies. In this study, we investigated the safety and feasibility of thoracoscopic uncommon segmentectomy. Methods: A total of 105 patients underwent thoracoscopic anatomic pulmonary segmentectomy in our department between March 2006 and September 2018. Among them, 37 received an uncommon segmentectomy and 68 received a common segmentectomy. Uncommon segmentectomy was defined as any segmentectomy, except for segmentectomies of the lingual, basilar, or superior segment of the lower lobe, or upper division of the left upper lobe. We retrospectively compared characteristics and perioperative outcomes between patients receiving uncommon versus common segmentectomy. Results: Uncommon segmentectomies were performed in the left S1+2 in nine patients, S3 in three, S9+10 in one, others including the sub-segment area in one, right S1 in four, S2 in six, S3 in two, S7+8 in two, S9+10 in six, and others including the sub-segment area in three. No significant differences were observed in patient characteristics between the two groups, or in perioperative results, including operative time, blood loss, postoperative drainage, hospitalization, morbidity, mortality, rate of conversion to thoracotomy, or rate of significant bleeding. No local recurrence was detected on the intersegmental plane in either group. Conclusions: Thoracoscopic uncommon segmentectomy is feasible and safe. It also helps ensure an oncological safety margin by division of the appropriate intersegmental plane.